The Impact of Brexit on EU Policies - De Ville, Ferdi (2019)
While the result of the UK’s referendum on membership of the EU has been the subject of considerable scholarly interest, relatively little has been written on the impact of Brexit on the EU. Where academics have addressed the issue, they have tended to either see Brexit through the lens of European ‘(dis)integration’ theory or focused on its ‘static’ effects, assessing the impact of removing the UK from the EU’s policymaking machinery based on its past behaviour. This editorial sets out the overarching rationale of this thematic issue and introduces some key analytical elements drawn on by the individual contributions. Given that Brexit has so far not set in train major EU disintegration, the focus is on the detailed impact of the UK’s exit across specific policy areas and on problematising the notion that it necessarily implies a more socially progressive turn in EU policies. Our starting point is the fundamental uncertainty surrounding the future EU–UK relationship, and the process of arriving there. This points to the importance of focusing on the ‘dynamic’ impacts of Brexit, namely adjustment in the behaviour of EU actors, including in anticipation of Brexit, and the discursive struggle in the EU over how to frame Brexit. Policy change may also occur as a result of small, ‘iterative’ changes even where actors do not actively adjust their behaviour but simply interact in new ways in the UK’s absence. Several of the issue’s contributions also reflect on the UK’s role as a ‘pivotal outlier’. The editorial concludes by reflecting on how we analyse the unfolding Brexit process and on what broader insights this thematic issue might offer the study of EU politics.